Modulation of a transcription factor counteracts heterochromatic gene silencing in Drosophila. - Ahmad, K.; Henikoff, S. (Cell, 2001)
Variegation is a common feature of gene silencing phenomena, yet the basis for stochastic on/off expression is unknown. We used a conditional system that allows probing of heterochromatin at a reporter GFP gene by altering GAL4 transcription factor levels during Drosophila eye development. Surprisingly, the frequency of gene silencing is exquisitely sensitive to GAL4 levels, as though binding site occupancy affects the silenced state. The silent state is plastic, as spontaneous derepression occasionally occurs in both mitotically active and differentiating cells. By simultaneously assaying expression of a nearby gene, we further show that the size of an activated region within heterochromatin is small. We propose that variegation occurs because heterochromatin inhibits the transient exposure of factor binding sites.